KISAH-KISAH ISRA'ILIYYAT - Zakaria Syafe,i (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2012)
Isra'iliyyat is all stories entering into interpretation (tafsir) based on the stories of C hristians, Jewish or others. Those stories are intentionally included into the interpretation by the enemies of Islam to corrupt Muslims' faith.The existence of Isra’iliyyat in the interpretation began from that a number of the Jews who converted into Islam couldn't totally leave all of their previous tenets and beliefs. As a result, their religious understanding and practices are .frequently mixed between Islam and their previous faith. These Isra'iliyyat stories entered and amended in the interpretation in the period of tabi'in and obtained a peak time in the period of tabi'it tabi'in without any coercive selection so that those stories are hardly ever refused.Tamim Ad-Dari, Abdullah bin Salam, Ka'ab al-ahbar, Wahab bin Munabbih,. Muhammad bin Sa'ib al-Ka/bi, Abdul Malik bin Abdul Aziz bin Juray: Muqotil bin Sulaiman, and Muhammad bin Manvan as-Suddi, the Jews priests who converted into Islam, are the main sources of the Isra’iliyyat stories. Isra’iliyyat can destruct the Muslims faith because it shows as if Islam were human creation, and could be inserted by the deviate imagination and thoughts. Moreover, it can also eliminate the Muslims trust toward the Salaf Ulama of the group of the companions and tabii·n. Besides, it can turn the Muslims notice to conduct a research and to reveal the great secrets oftheQur'an.